Eksperimen Pembelajaran Matematika dengan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) dan Talking Stick Terhadap Hasil Belajar Matematika Ditinjau dari Keaktifan - Suci, Vivi Shinta, Muhammad Noor Kholid, S.Pd., M.Pd (2017)
This study aimed to analyze: (1) in the effect of the application of learning model Numbered Head Together (NHT), Talking Stick and Expository the learning outcomes of mathematics, (2) in the influence of thr students acivity to the learning outcomes of mathematics, (3 ) efect the interaction between the application of the learning model Numbered Head Together (NHT), Talking Stick and Expository with the level of student activity on learning outcomes in mathematics. This research was quantitative with quasi-experimental research design. The population in this study were all students of class VII MTs Muhammadiyah 6 Karanganyar Academic Year 2016/2017. The sampling technique in this study using cluster random sampling. Methods of data collection using achievement test and documentation. Data were analyzed using two-way analysis of variance with different cells. The results of the analysis with a significance level of 0.05 indicates that: (1) there are in the effect of learning model Numbered Head Together (NHT), Talking Stick and Expository the mathematics learning outcomes with Fa = 3.4437 (2) there are in student activity levels beginning with the results of learning mathematics by Fb = 16.4781 (3) there is no efect interaction between the learning model Numbered Head Together, Talking Stick and Expository with the level of student activity on learning outcomes of mathematics,with Fab=0.7343. Keywords: expository, math learning outcomes, student activity, numbered heads together, talking stick